(untitled) (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
Currently, the primary form of high-grade highways is constituted by asphalt concrete pavement. Winter conditions often result in ice and snow accumulation on these pavements, precipitating severe traffic incidents. Statistically, around 15%-30% of such incidents are directly linked to icy and snowy conditions. Hence, when roads are laden with ice and snow, the most cost-effective and efficient countermeasure remains the dispersal of deicing salt onto the road surface. Particularly in China’s northwestern region, which experiences low precipitation and consistent droughts, the deicing salts applied during winter aren’t diluted or transported away by water flow. Consequently, the soil surrounding the roads retains a higher concentration of deicing salts than other regions, leading to a pronounced impact on the pavement’s service life. This investigation aims to experimentally emulate the impact of this high-salt environment on the mechanical properties of asphalt mixtures, followed by an analysis of the crucial factors that influence the asphalt mixtures’ durability. The current study employs measures such as high-temperature rut testing, Marshall water immersion testing, and freeze-thaw splitting testing to investigate the damage patterns of mechanical properties in asphalt mixtures under varying grading, diverse deicing salt solutions, and differing frequencies of dry-wet cycles. In addition, the study employs grey correlation entropy analysis to ascertain the interdependence among factors influencing the performance of asphalt mixtures. The findings reveal that after undergoing 0, 5, 10, 15, 20, 25, and 30 dry-wet cycles in solutions of 20% industrial salt (NaCl), 15% urea (CH4N2O), and 20% anhydrous ethanol (CH2CH3OH), both the high-temperature stability and water stability of asphalt mixtures with AC-13 and AC-16 gradings displayed varying levels of decline. Overall, an enhancement in the fine aggregate percentage in asphalt mixtures can augment the asphalt concrete’s resistance to deicing salt erosion. As per the grey correlation entropy analysis, gradation variances exerted the most significant impact on diverse mechanical properties, followed by the type of deicing salt solution, with the least significant impact attributed to the frequency of dry-wet cycles. Thus, judicious selection of road materials and structural design can effectively counter the erosive action of deicing salts, thereby enhancing the service life of the road surface.